The Internal Decay of Wood Is Driven by the Interplay Between Foraging Magellanic Woodpeckers and Environmental Conditions - Vergara-Egert, P; Quiroz-Espinoza, M; Fierro-Tapia, C; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M; Zuñiga-Alvarez, A; Hidalgo-Corrotea, C (Elsevier B.V., 2024)
Although woodpeckers are known to forage in decaying trees, their contribution to internal wood decay is not well known. In this sense, non-destructive techniques for structural wood degradation provide an opportunity to quantitatively assess the role of woodpeckers in tree decay. We used sonic tomography to test that the trunks of living trees pecked by Magellanic woodpeckers show pronounced decay, which accelerates under environmental conditions favorable to wood-decaying fungi. The internal decomposition of wood and its decay rate were measured over four years on 156 living southern beech (Nothofagus) trees belonging to four dominant species of southern temperate forests in northern Patagonia. Half of these live trees had woodpecker feeding holes, while the rest served as controls. The percentage of decayed wood, although not severely decayed, increased in sections with the presence of woodpecker holes, but was also influenced by temperatures and biophysical variables such as elevation and topography. The trunk sections with woodpecker holes and exposed to intensive foraging showed accelerated inter-annual decay. Woodpecker foraging activity interacted with vegetation characteristics, resulting in accelerated wood decay in forest sites with an open canopy and exposed to water stress. Thus, sonic tomography provided evidence of a close relationship between woodpeckers and internal wood decomposition, suggesting a positive feedback mechanism regulated by forest disturbance. The approach used here can be extended to gain insight into the influence of woodpeckers on tree decay and mortality in regions experiencing severe drought and forest degradation, such as northern Patagonia. © 2024 Elsevier B.V.